Bronchobiliary fistula after ablation of hepatocellular carcinoma adjacent to the diaphragm: Case report and literature review - Zhi‐mei Huang; Meng‐xuan Zuo; Yang‐kui Gu; Chun‐xiao Lai; Qiu‐xiang Pan; Xiao‐cheng Yi; Tian‐qi Zhang; Jin‐hua Huang (Thoracic Cancer)
Background Bronchobiliary fistula is a rare, but life‐threatening complication after ablation of hepatocellular carcinoma. Few cases of bronchobiliary fistula have been reported and the treatment is controversial. Methods From 2006 to 2019, a total of 11 patients were diagnosed with bronchobiliary fistula after ablation and received nonsurgical treatment. Results All 11 patients presented with cough and bilioptysis. There were only two patients in which MRI revealed an obvious fistulous tract connecting the pleural effusion and biliary lesions. Pleural effusion, liver abscess and hepatic biloma were found in other patients. Three patients died of uncontrolled bronchobiliary fistula. Conclusions Bronchobiliary fistula is a rare post‐ablation complication but should be taken into consideration in clinical decisions. Minimally invasive interventional treatment is a relatively effective means of dealing with bronchobiliary fistula, but as for the more severe cases, greater clinical experience is required.